Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This is a bit of a basic computational question concerning Lie algebras, but I'm getting kind of bamboozled so I thought I'd post it.

I'm confused about how to perform some computations in Serre's Complex Semisimple Lie algebras. The first case is the following: Let $X,Y,H$ be a basis for $\mathfrak{sl}_2(\mathbb{C})$ satisfying the usual commutation relations: $[H,X] = 2X$, $[H,Y] = -2Y]$, and $[X,Y] = H$. Then the claim is that for any representation of $\mathfrak{sl}_2(\mathbb{C}))$, if

$$ \Theta = e^Xe^{-Y}e^X $$

then

$$ \Theta H = -H \Theta, \Theta X = - Y \Theta, \Theta Y = - X \Theta. $$

I started trying to force this out with the commutation relations, but I got $[e^X, H] = H - 2Xe^X$ so that

$$ \Theta H = e^X e^{-Y} (He^X + -2Xe^X). $$

At this point, I became overwhelmed with the prospect of trying to commute $X$ with $e^Y$.

How do you do these computations???

Secondly, Serre also states the following. Let $\mathfrak{g}$ be a Lie algebra which decomposes under the action of a Cartan subalgebra $\mathfrak{h}$ as $$ \mathfrak{g} = \mathfrak{h} \bigoplus_{\alpha} \mathfrak{g}^{\alpha} $$ and let $X_{\alpha} \in \mathfrak{g}^{\alpha} , Y_{\alpha} \in \mathfrak{g}^{-\alpha}, H_{\alpha} \in \mathfrak{h}$ be elements satisfying the commutation relations as above. Then $$ e^{X_{\alpha}}e^{-Y_{\alpha}}e^{X_{\alpha}} $$ restricts on $\mathfrak{h}$ to be the usual reflection associated to $\alpha$, i.e. negating the root $\alpha$ and fixing the hyperplane determined by $\alpha$.

It's an easy computation to see that the above element does indeed fix the orthogonal hyperplane, but I don't know how to show the rest.

How can one see this?

share|improve this question
    
Since $X$, $Y$, $H$ are fixed elements of $sl_2(\mathbb{C})$, I don't understand the part where you say "in any representation of $sl_2(\mathbb{C})$". –  Ted May 3 '12 at 7:10
1  
For the second, shouldn't be $e^{\operatorname{ad}X_\alpha}e^{-\operatorname{ad}Y_\alpha}e^{\operatorname{ad}‌​X_\alpha}$? –  Yuki Jul 20 '12 at 15:00
add comment

1 Answer 1

First Part

(I assume that really $X\equiv d(X)$ for some representation $d$; this makes no odds.)

You're apparently familiar with the fact that $[[H,Y],Y]=0$ gives (inductively) $$[H,Y^n]=nY^{n-1}[H,Y]$$

Another inductive argument (which can in fact be generalized) would show $$[X,Y^n]=n(H+(n-1))Y^{n-1}$$


However there is a more satisfying approach involving showing

$$\boxed{e^{A}Be^{-A}=B+[A,B]+\frac{1}{2!}[A,[A,B]]+\frac{1}{3!}[A,[A,[A,B]]]+\cdots}$$

(Wikipedia points out that this is essentially equivalent to $e^{\textrm{ad}(A)} B$ in the case of the fundamental representation.)

Proof: Write $f_B(\lambda)=e^{\lambda A}Be^{-\lambda A}$. Then $$f_B'(\lambda)=e^{\lambda A}(AB-BA)e^{-\lambda A} = f_{[A,B]}(\lambda)$$ Inductively, we find $$f_B^{(n)}(\lambda) = f_{[A,\cdots [A,B]\cdots]}(\lambda)$$ Setting $\lambda=1$ and using the Taylor expansion of $f_B(1)$ gives the result. QED.


This generalizes the identity you already used. It is useful because, setting $A=Y,B=X$, we find $[A,B]=-H$ and so $[A,[A,B]]=[Y,-H]=-2Y$, and finally $$\boxed{[A,[A,[A,B]]]=[Y,-2Y]=0}$$ so the series terminates. You should be able to use this to compute the result you want.


Second Part

To see that the root is negated, I think you're simply supposed to use the definition of the action of group elements on the Lie algebra to observe that $$\Theta H_\alpha \Theta^{-1} = -H_\alpha \Theta \Theta^{-1} = -H_\alpha$$ You can use the $X,Y$ as well if you like.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.